PENGEMBANGAN MEDIA PEMBELAJARAN LITERASI MELALUI DONGENG DALAM PEMBELAJARAN BAHASA INDONESIA KELAS V DI SEKOLAH DASAR - sulastri; Bukman Lian; Liza Murniviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce literacy learning media through fairy tales in Indonesian language learning for grade V in Elementary Schools that are valid and practical. The method in this study uses the Research & Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation and evaluation. Data collection used in the form of observation sheets, expert validation questionnaires and student response questionnaires and tests. Based on the results of data assessment using media expert validation, a percentage of 85.45% was obtained with a very valid category, material expert validation obtained a percentage value of 80% with a very valid category and for language expert validation obtained a percentage value of 87.5% with a valid category then the results of the student response questionnaire analysis from the one to one results obtained an average value of 83.33% with a very practical category, in the small group results obtained 81.45%, with a very practical category. Thus it can be concluded that literacy learning media through fairy tales in Indonesian language learning for grade V in Elementary Schools can be said to be valid and practical